2007
DOI: 10.1007/s11103-007-9218-z
|View full text |Cite
|
Sign up to set email alerts
|

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population

Abstract: With the completion of the rice genome sequencing project, the next major challenge is the largescale determination of gene function. As an important crop and a model organism, rice provides major insights into gene functions important for crop growth or production. Phenomics with detailed information about tagged populations provides a good tool for functional genomics analysis. By a T-DNA insertional mutagenesis approach, we have generated a rice mutant population containing 55,000 promoter trap and gene act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 31 publications
0
49
0
Order By: Relevance
“…T-DNA AT populations have been developed using vectors with cauliflower mosaic virus 35S enhancer multimers, the inserts characterized by FSTs and phenomic data for forward and reverse genetics screens (Jeong et al, 2002;Chern et al, 2007;Hsing et al, 2007;Wan et al, 2009). Recently, an Ac-Ds AT system has also been developed (Qu et al, 2008) using convenient markers for selection of multiple transposants from a few starter transformed lines.…”
Section: Activation Taggingmentioning
confidence: 99%
“…T-DNA AT populations have been developed using vectors with cauliflower mosaic virus 35S enhancer multimers, the inserts characterized by FSTs and phenomic data for forward and reverse genetics screens (Jeong et al, 2002;Chern et al, 2007;Hsing et al, 2007;Wan et al, 2009). Recently, an Ac-Ds AT system has also been developed (Qu et al, 2008) using convenient markers for selection of multiple transposants from a few starter transformed lines.…”
Section: Activation Taggingmentioning
confidence: 99%
“…However, the challenge will remain to accurately associate changes in these molecules with quantifiable developmental and physiological stress adaptation phenotypes and thus allow genotype-tophenotype predictions to be made. To achieve this goal, deep phenotyping (phenomics) is essential to allow compilation of precise multidimensional, morphological, physiological, and molecular phenotypes of plant responses (Boyes et al, 2001;Granier et al, 2006;Chern et al, 2007;Miyao et al, 2007;Kuromori et al, 2009;Furbank and Tester, 2011). Although Arabidopsis and E. salsugineum possess some fundamental differences in developmental program such as a vernalization requirement for promotion of flowering in E. salsugineum (Bressan et al, 2001), their developmental growth stages from seed to rosette leaves to production of flowering bolts are similar, a feature that facilitates phenotypic comparison between the two species.…”
mentioning
confidence: 99%
“…Jeon et al (2000) have investigated the phenotypic variation of rice T-DNA tagging lines and found that up to 17% of the lines were sterile and various mutant phenotypes were observed including dwarfing, leaf-pigment alterations, tallness and so on. Chern et al (2007) reported 11 categories of the visible phenotypic variations with the ratio at around 18%. Miyao et al (2007) have investigated around 50,000 Tos17 insertion lines and found that nearly half of the lines showed mutant phenotype.…”
Section: Rice Mutant Resources and Databases For Rice Functional Genomentioning
confidence: 99%